SenseCam: A Wearable Camera can Help Improve Autobiographical Memory in Patients with Alzheimer's Disease - Browne, Georgina; Berry, Emma; Hodges, Steve; Williams, Lyndsay; Smyth, Gavin; Kapur, Narinder; Butler, Alex; Woodberry, Ken (Microsoft Research, 2007)
A wearable camera can help improve autobiographical memory in patients with Alzheimer’s disease.
Presentation at the Institute of Physics and Engineering in Medicine: Annual Scientific Meeting 2007, Cardiff